2017
DOI: 10.3844/ojbsci.2017.50.57
|View full text |Cite
|
Sign up to set email alerts
|

Studying Interrelation of PDLIM4 with the Model of CD74-Mediated Development of Breast Cancer

Abstract: Mammary gland tumors are often characterized by deregulation of RIL/PDLIM4 expression, however, PDLIM4-mediated mechanisms of cancer development still remain unknown. The aim of our research was to study the influence of PDLIM4-deregulation on transcript me changes of malignized cells. We performed а comparative NGS-analysis of breast cancer cell lines with suppressed and induced expression of PDLIM4 and identified a number of genes, whose expression correlated with PDLIM4 level. Among them we found CD74 gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This assumption is consistent with the results of our previous study, which revealed that RIL overexpression correlated with the unfavorable prognostic parameters of tumors, namely an increased CD74 level, reduced expression of E-cadherin, and inactivated intracellular tumor suppressor protein Scribble. Although the RILdependent mechanisms of tumor formation remain elusive, RIL may be involved in breast cancer development through the CD74-mediated mechanism typical of malignant cells [16] where increased expression of CD74 could lead to a mislocalization and inactivation of Scribble and loss of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption is consistent with the results of our previous study, which revealed that RIL overexpression correlated with the unfavorable prognostic parameters of tumors, namely an increased CD74 level, reduced expression of E-cadherin, and inactivated intracellular tumor suppressor protein Scribble. Although the RILdependent mechanisms of tumor formation remain elusive, RIL may be involved in breast cancer development through the CD74-mediated mechanism typical of malignant cells [16] where increased expression of CD74 could lead to a mislocalization and inactivation of Scribble and loss of E-cadherin.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, a growing body of data suggests that RIL may also act as an oncogene [16][17][18]. The most aggressive breast cancer cell lines MDA-MB-231, MDA-MB-436, and BT-474 have high levels of RIL expression concomitant with unfavorable prognostic parameters, such as the increased CD74 and low E-cadherin levels [16]. These effects are not explained by the RIL-mediated attenuation of Src activity and call into question whether this model it universally applicable.…”
Section: Introductionmentioning
confidence: 99%